O discurso político na mídia televisiva: uma análise do segundo turno das eleições de 2008 para a Prefeitura de Pelotas - Bertinetti, Mariana Loureiro Duarte (2012)
The present study aims at analyzing the discursive constructions of the candidates for Mayor of Pelotas, Fetter Jr and Fernando Marroni, in the second round of municipal elections of 2008, at the Free Time Election Propaganda (HGPE) in television media, especially related to the more used themes in this campaign: health and asphalt. The subject of health, always highlighted in election campaigns because of the importance in people's lives, was addressed in order to highlight what each candidate did while he was in the position of the situation and what his opponent did not perform while he held office. The issue of asphalt gained prominence due to an amount arising out of international finance, whose authorship of the project, as well as its content, were the central theme of the speeches. Besides trying to understand the articulatory practice used by each candidate to hegemonize their discourses and visualize the existing antagonistic cut, the study also seeks to analyze the rhetorical strategies used by each one trying to persuade the voters viewers. For the analysis related to these themes, the research's main theoretical concepts are Ernesto Laclau and Chantal Mouffe's discourse theory. Seeking to support the discursive behavior of these candidates in this theoretical approach, this paper seeks to understand not only the construction of discourses, but also see its use specifically in television media. This dissertation as a whole, is a set of theories and empirical analyses that seek to approximate the areas of political science and media, to give an overview of marketing activity in the construction of political speeches to television and thus colaborating the understanding of this issue so present in contemporary democratic processes